Analysis of Accounting Information Systems in Javanese Kluwak Sweet Soy Sauce MSME - Zaimar, Fina Ruzika; Adriansyah, Adriansyah (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2025)
This study aims to analyze the application of the accounting information system cycle in the Kecap Manis Kluwak Jawa. The method used is a qualitative method with data collection techniques, namely interviews, observations and documentation. Through the results of the interview, it was identified that the owner of Kecap Manis Kluwak Jawa MSMEs still uses traditional methods in recording and reporting financial reports. This can result in errors in data and information management, as well as hinder business growth. This study underlines the importance of applying good accounting theories in MSME financial management, such as the double-entry system, which is the basis for business actors to record transactions accurately and transparently. Therefore, it is recommended to implement the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) as a policy that must be followed by MSMEs. This policy aims to increase the transparency and accountability of financial statements, so that it can increase the trust of investors and creditors. Therefore, this study contributes to the understanding of how accounting information systems can be applied effectively in MSMEs in Kecap Manis Kluwak Jawa Keywords: Accounting Information System Cycle; SAK EMKM; MSMEs